Study on the Swelling Behavior of Clayey Soil Blended with Geocell and Jute Fibre - Sanjeev Kumar; Anil Kumar Sahu; Sanjeev Naval (Salehan Institute of Higher Education, 2021)
Expansive soils like clays undergo swelling that can both be detrimental and acceptable in different applications. In the Northern part of India, especially Delhi region, natural soils containing clays & clayey sands support most of the buildings. Mechanically stabilized clays mixed with sand are used for local earthwork construction such as roads and landfills. Exact understanding of the swelling behaviour of such soils is a pre-requisite before the start of any construction projects. In this paper the swelling behaviour of clayey soil reinforced with geocell & Jute fibres has been presented. The laboratory investigations include one dimensional swelling tests using California Bearing Ratio (CBR) mould to study the swelling properties for different mix proportions. The maximum decrease in swelling potential of Geocell reinforced specimens was observed at fibre content of 0.80 percent and 40mm fibre length, beyond which increase in the swelling potential and swelling pressure has been observed. With this optimal reinforcement, a reduction of 71.24 percent in swelling and 41.10 percent in swelling pressure has been observed as compared to unreinforced soils. The study provides a solution towards the treatment of expansive soils before starting any construction activity over such soils and a step towards mitigating disasters related to infrastructure facilities grounded on expansive soils. Doi: 10.28991/cej-2021-03091728 Full Text: PDF